Introducing 4-(2-ethylhexyl)dithieno[2,3]pyridine as a novel π-bridge in indolocarbazole-based sensitizers for high-performance single and tandem dye-sensitized solar cells - Al-Furaiji, Qasim Chyad Abdulzahra; Hasan, Hiba Ali; Al-Mehana, Wisam Naji Atiyah; Alraih, Alhafez M.; Ahmed Mohammed, Mohammed; Abdulkareem-Alsultan, G.; Nassar, Maadh Fawzi (Elsevier, 2025)
The modification of highly conjugated heterocyclic π-bridges is an effective approach to enhance light absorption and charge transfer in dye-sensitized solar cells (DSSCs). Here, we report two indolocarbazole-based sensitizers, ICS-1 and ICS-2, featuring 4-(2-ethylhexyl) dithieno [2,3] pyridine as a highly conjugated π-bridge and squaraine-indoline-5-carboxylic acid as the strong electron-withdrawing and anchoring unit to construct a (D-π-A) system. The chemical structures of all intermediates and final ICS 1–2 dyes were confirmed through extensive spectroscopic investigations. Density functional theory (DFT) and time-dependent DFT (TD-DFT) studies were performed for the initial identification of energy levels, electronic structure and optical properties. Ultraviolet–visible spectrophotometry (UV–vis) absorption measurements demonstrated broad spectra in the 545–635 nm range, yielding experimental optical band gaps of 2.15 eV for ICS-1 and 1.86 eV for ICS-2. The results indicate enhanced intramolecular charge transfer in ICS-2, attributed to a more extensive π-bridge with benzothiadiazole. J–V results revealed that ICS-2 yield higher power conversion efficiency (PCE) of 8.50 % (VOC = 0.858 V, FF= 0.516 andJSC=19.20 mA/cm-2) than of ICS-1 (6.95 %), aligned with decreased recombination and extended electron lifetimes. Furthermore, ICS-2 was used in parallel tandem DSSCs with N719, where the N719 (top)/ICS-2 (bottom) configuration provided an impressive PCE of 13.55 % (VOC = 0.888 V, FF = 0.675 andJSC=22.61 mA/cm-2), outperforming the reversed arrangement (10.48 %). Long-term stability tests under continuous illumination (1000 h) showed 98.9 % retention of the initial PCE for ICS-2 while TD-N719/ICS-2 demonstrated 99.4 % emphasizing the durability of ICS-2 and tandem devices. This study demonstrated that the rational modification of indolocarbazole-based (D–π–A) dyes, combined with tandem device engineering, provides a robust pathway toward highly efficient and stable DSSCs.